Improving Cardiovascular Follow-Up after Diagnosis of a Hypertensive Disorder of Pregnancy using the Electronic Health Record. Issue 3 (May 2023) - Burgess, Adriane; Stover, Samantha
Abstract: Background: Cardiovascular disease is the leading cause of death among women. Sex-specific risk factors for cardiovascular disease include history of a hypertensive disorder of pregnancy. Problem: After diagnosis of a hypertensive disorder of pregnancy, professional societies recommend follow-up with a primary care provider for preventative care. There are gaps in patient and health care provider knowledge of the association between a hypertensive disorder of pregnancy and cardiovascular disease. That gap has a negative effect on patients receiving recommended follow-up. Methods: An electronic registry was created to identify those who gave birth in our health system and had a diagnosis of hypertensive disorder of pregnancy. From this, information outreach was sent electronically to the patient and their primary care provider. Interventions: Communication in the outreach included education on the association between hypertensive disorders of pregnancy and cardiovascular disease, the importance of follow-up, cardiopreventative strategies, and biochemical assessment. Medical records were audited at approximately 6 months postpartum to determine if patients completed a visit with their primary care provider to discuss cardiovascular risks. Results: Between May 2021 and June 2022, 15% ( n = 1, 131) of patients who gave birth in our health system had a diagnosis of hypertensive disorder of pregnancy. Ninety percent of those patients who received outreach communication viewed the letter. At baseline, 16% of patients during postpartum with a hypertensive disorder of pregnancy saw their primary care provider to discuss cardiopreventative strategies. After implementation of our program, 26% of those with a hypertensive disorder of pregnancy saw their primary care provider for follow-up and discussed cardiopreventative strategies. Clinical Implications: Nurses should ensure that women during postpartum and their primary care providers are educated about the association of hypertensive disorders of pregnancy and long-term cardiovascular risk. The electronic health record may be an optimal way to ensure education is provided and follow-up scheduled. Abstract : Cardiovascular disease is one of the leading causes of morbidity and mortality among women in the United States. A diagnosis of hypertensive disorder of pregnancy can increase risk of cardiovascular disease later in life. Preventative measures and healthy lifestyle changes, if initiated during postpartum and continued, can be beneficial. In this quality improvement project, women who were diagnosed with a hypertensive disorder of pregnancy were followed up during postpartum using the electronic health record with information about the links between hypertension during pregnancy and risk of cardiovascular disease and offered educational resources on a healthy lifestyle. Their primary care providers were notified about their diagnosis of a hypertensive disorder of pregnancy and encouraged to discuss the implications for future health with these new mothers.